Ordinary heterotrophic organisms with aerobic storage capacity provide stable aerobic granular sludge for C and N removal. (15th April 2022) - Fall, C.; Barrón-Hernández, L.M.; Gonzaga-Galeana, V.E.; Olguín, M.T.
Abstract: The study investigated the mechanisms and microbial communities underlying the long-term stability and removal performances shown by aerobic granular sludge (AGS) reactor involving polyhydroxyalkanoates (PHA) aerobic-storing bacteria. The characteristics of the sludge, removal performances and bacterial community structure were determined. The prevailing metabolic phenotype was similar in the parent conventional activated sludge (CAS) reactor and its upgraded AGS version, showing high COD and NH4 uptake, versus low P and N reduction. Polyphosphate and glycogen accumulating organisms, PAO and GAO, were not enriched in the reactors despite initial targeting of anaerobic-aerobic cycle. Instead, PHA-aerobic storing bacteria ( Thauera and Paracoccus ) were dominant, but revealing a stable AGS system for BOD and N removal. The PAO/GAO failed selection and Thauera overgrowth were analyzed for beneficial use in developing alternative AGS technology for BOD and N removal applications. Graphical abstract: Well granulated and stable AGS with dominance of OHOs (PHA storing). Image 1 Highlights: Not all ordinary heterotrophs (OHO) harm aerobic granular sludge (AGS) stability. Polyhydroxyalkanoate (PHA) aerobic-storing OHOs were dominant: Thauera, Paracoccus . High oxygen and no-denitrification can shift AGS from PAO to PHA-storing OHOs. As relative slow growers and polymer secretors, PHA-storing OHOs stabilize granules. Technological AGS niche based on PHA-storing OHOs is potential alternative.